2018
DOI: 10.1038/s41514-018-0027-1
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Repeat dose NRPT (nicotinamide riboside and pterostilbene) increases NAD+ levels in humans safely and sustainably: a randomized, double-blind, placebo-controlled study

Abstract: The original version of the published Article contained an incorrect citation for reference 20 “Hubbard, B. P. & Sinclair, D. A. Measurement of sirtuin enzyme activity using a substrate-agnostic fluorometric nicotinamide assay. Methods Mol. Biol. 1077, 167–177 (2013).” The citation for reference 20 has been changed to “Cheng, Y. et al. SIRT1 activation by pterostilbene attenuates the skeletal muscle oxidative stress injury and mitochondrial dysfunction induced by ischemia reperfusion injury. Apoptosis 21 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Animal studies showed that NR is able to increase plasma and tissue NAD + concentrations ( 8–13 ). Also in humans, NR is able to increase circulatory NAD + metabolites after several dosages ranging from 100 mg/d to 2000 mg/d ( 17–20 ). Here, we used a dosage of 1000 mg/d for 6 wk, and in line with other data presented we did not report side effects during 6 wk 1000 mg NR/d supplementation ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies showed that NR is able to increase plasma and tissue NAD + concentrations ( 8–13 ). Also in humans, NR is able to increase circulatory NAD + metabolites after several dosages ranging from 100 mg/d to 2000 mg/d ( 17–20 ). Here, we used a dosage of 1000 mg/d for 6 wk, and in line with other data presented we did not report side effects during 6 wk 1000 mg NR/d supplementation ( 17 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also in humans, NR is able to increase circulatory NAD + metabolites after several dosages ranging from 100 mg/d to 2000 mg/d ( 17–20 ). Here, we used a dosage of 1000 mg/d for 6 wk, and in line with other data presented we did not report side effects during 6 wk 1000 mg NR/d supplementation ( 17 , 19 ). We investigated if NR supplementation was able to increase the NAD + metabolome in skeletal muscle tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same dose, however, failed to elicit effects on insulin parameters and glucose tolerance after 3 months in non-diabetic obese men ( 177 ). Daily supplementation of 500 mg NR with a detectable increase in NAD + serum levels did not cause serious adverse effects after 8 weeks ( 173 ). This was corroborated by a 6 week long study supplementing NR, via a commercially available supplement, which also found reduced systolic/diastolic blood pressure and arterial stiffness ( 178 ).…”
Section: Nad + Precursorsmentioning
confidence: 99%